1997
DOI: 10.1007/bf02467122
|View full text |Cite
|
Sign up to set email alerts
|

Gas nitriding in catalytically prepared ammonia media

Abstract: Chemical heat treamaent of machine parts and tools in gas media at 500 -600~ is widely used in the industry. However, the obvious advantages of the method are accompanied by certain serious disadvantages that reduce the range of its application. The present work is an attempt to realize a new approach to gas nitriding, solve some problems of the process, and widen the field of its application.During the 70 years of industrial use of the methods of low-temperature chemical heat treatment (CHT), various processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The results of our earlier studies [5,6] have shown that the formation of pores in the carbonitride layer is most probably caused by the liberation of excess nitrogen in a stable gaseous form. In specimens nitrided at a potential o1"5 and 6% no visible changes in the microstructure occurred prior to a 400and 470-h hold respectively.…”
Section: Methods Of Experiments and Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our earlier studies [5,6] have shown that the formation of pores in the carbonitride layer is most probably caused by the liberation of excess nitrogen in a stable gaseous form. In specimens nitrided at a potential o1"5 and 6% no visible changes in the microstructure occurred prior to a 400and 470-h hold respectively.…”
Section: Methods Of Experiments and Discussion Of Resultsmentioning
confidence: 99%
“…Such a process has been created on the basis of nitriding in catalytically prepared ammonia furnace atmospheres [5,6], which opens new possibilities {br low-temperature CHT. This method of gas nitriding has made it possible to control not only the phase composition of the surface carbonitridc layer of the nitrided metal but also the concentration of nitrogen in the carbonitride.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The results of these studies fully confirmed the validity of the initial assumptions: the nitriding process radically changed its character in the regime parameters and in the quality of the processed item. Upon installation of a catalytic reactor equipped with a SGFWC cassette assembly on the ammonia or ammonia−air line of the nitriding furnace provided a radical activation of the furnace atmosphere, which manifested itself through the following features of the nitriding of metal surfaces [18,19]:…”
Section: Sgfwc-assisted "Catalytic" Nitridingmentioning
confidence: 99%
“…Most stainless-steel alloys exhibit a three-layer structure during nitridation, which can be observed under optical magnification. The layers consist of the subsurface, typically composed of the ε phase, the second layer comprised of metastable phases (ϒ-N) and expanded martensite (α-N) with precipitates of MN-type nitrides (often CrN), and the deeper zone adjacent to the steel core enriched with carbon [5] [6]. Two mechanisms are considered for simultaneous penetration and the formation of a solid solution or interaction of nitrogen in the metal structure: physical diffusion and chemical gas-metal reaction.…”
Section: Introductionmentioning
confidence: 99%